2021
DOI: 10.3390/vetsci8020034
|View full text |Cite
|
Sign up to set email alerts
|

Swine Small Intestine Sealing Performed by Different Vessel Sealing Devices: Ex-Vivo Test

Abstract: This study aimed to evaluate the sealing quality of swine small intestine using different laparoscopic radiofrequency vessel sealing devices (two 5 mm: RFVS-1 and -2; one 10 mm: RFVS-3) and a harmonic scalpel (HS) compared to golden standard closure technique. The study was divided into two arms. In study arm 1: n = 50 swine intestinal loops (10 per group) were transected with each instrument and the loops in which the devices provided complete sealing, at the gross inspection, were tested for maximum burst pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
(63 reference statements)
0
3
0
Order By: Relevance
“…Previous studies in rat, pig, and human intestines have demonstrated the efficiency of RFDs in performing intestinal anastomoses in both in vivo and ex vivo models 8,10–19 . According to these studies, RFDs are efficient, easy to use, and appear to be sufficient as a stand‐alone method for performing intestinal anastomoses in ex vivo models, with a bursting pressure similar to that obtained with a stapler 13 …”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Previous studies in rat, pig, and human intestines have demonstrated the efficiency of RFDs in performing intestinal anastomoses in both in vivo and ex vivo models 8,10–19 . According to these studies, RFDs are efficient, easy to use, and appear to be sufficient as a stand‐alone method for performing intestinal anastomoses in ex vivo models, with a bursting pressure similar to that obtained with a stapler 13 …”
Section: Discussionmentioning
confidence: 97%
“…Previous studies in rat, pig, and human intestines have demonstrated the efficiency of RFDs in performing intestinal anastomoses in both in vivo and ex vivo models. 8,[10][11][12][13][14][15][16][17][18][19] According to these studies, RFDs are efficient, easy to use, and appear to be sufficient as a stand-alone method for performing intestinal anastomoses in ex vivo models, with a bursting pressure similar to that obtained with a stapler. 13 In the current study, the use of RFD maintained the intestine in position during completion of the anastomosis and was similar in construction time to other methods for jejunocecal anastomosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation